Pengembangan Proses Identitas Guru SD Negeri 001 Kebuh Tengah Melalui Self-Control dan Nilai-Nilai Pribadi - Sukenti, Desi; Syahraini Tambak; Alber; Sylvia Pratama Devi (UIR Press, 2023)
Controlling emotions and behavior is a crucial aspect to be carefully considered in developing the teacher's identity by strengthening self-control and personal values that serve as values and impact students. This is the key issue in this community service. Therefore, self-control and personal values need to be stimulated in all learning activities at school. This community service aims to develop the identity of teachers through self-control and the values possessed by teachers. Participatory action research is the method used in the implementation of this community service. The community service results in the development of the identity of teachers at SD 001 in Kebuh Tengah through self-control and personal values in preparing materials in accordance with the cultural conditions of the surrounding community, namely Malay culture. It involves creating teaching materials integrated with the observed local culture and designing lesson plans that align with the demands of learning objectives. The data collection technique used is conducting interviews with elementary school teachers with prepared questions to explore issues related to self-control and personal values that need to be strengthened in teachers. Strong self-control has an impact on teachers in restraining or controlling oneself, namely the ability to control behavior, cognitive control, and decision-making control. Meanwhile, personal values are also closely related to teachers in providing instructional materials to students. The personal values that teachers should master include self-transcendence, conservation, self-improvement, and openness to change. This community service concludes that developing the teacher's identity can be achieved by integrating self-control and personal values.